Factors associated with esophageal candidiasis and its endoscopic severity in the era of antiretroviral therapy. - So Nishimura; Naoyoshi Nagata; Takuro Shimbo; Naoki Asayama; Junichi Akiyama; Norio Ohmagari; Hirohisa Yazaki; Shinichi Oka; Naomi Uemura (PLoS ONE, 2013)
Candidia esophagitis (CE) is an AIDS-defining condition, usually occurring in individuals with low CD4 counts of <200 cells/µL. Endoscopy is a valuable definitive diagnostic method for CE but may not be indicated for asymptomatic patients or for those with high CD4 counts or without oral candidiasis. This study assessed such patients to clarify the factors associated with CE and its severity on endoscopy in the highly active antiretroviral therapy (HAART) era.A total of 733 HIV-infected patients who underwent upper gastrointestinal (GI) endoscopy were analyzed. Sexual behavior, CD4(+) count, HIV-RNA viral load (VL), history of HAART, GI symptoms, GI diseases, and oral candidiasis were assessed. Endoscopic severity of CE was classified as mild (Kodsi's grade I/II) or severe (grade III/IV). Of the 733 subjects, 62 (8.46%) were diagnosed with CE (mild, n = 33; severe, n = 29). Of them, 56.5% (35/62) had no GI symptoms, 30.6% (19/62) had CD4 + ≥200 cells/μL, and 55.3% (21/38) had no oral candidiasis. Univariate analysis found lower CD4+ counts, higher HIV VL, and no history of HAART to be significantly associated with CE. With lower CD4(+) counts and higher HIV VL, CE occurrence increased significantly (P<0.01 for trend in odds). Multivariate analysis showed low CD4+ counts and high HIV VL to be independently associated with CE. Of the severe CE patients, 55.2% (16/29) had no GI symptoms and 44.4% (8/18) had no oral candidiasis. Median CD4(+) counts in severe cases were significantly lower than in mild cases (27 vs. 80; P = 0.04).Low CD4+ counts and high HIV VL were found to be factors associated with CE, and advanced immunosuppression was associated with the development of severity. Endoscopy is useful as it can detect CE, even severe CE, in patients without GI symptoms, those with high CD4 counts, and those without oral candidiasis.